Work Passion: Bagaimana Kelanjutannya pada Sepuluh Tahun Terakhir - Ilham Medal Junjunan; Sinta Ayuliani (LPPM UNIBI, 2021)
Research on work passion has become an interesting topic in the development of science, especially in the field of organization. Work passion refers to the high level of passion and enthusiasm that individuals feel towards their work. This concept involves feelings of enthusiasm, deep involvement, and strong commitment to the task at hand. In this study, attention is paid to how work passion influences individual behavior at work, job performance, job satisfaction, motivation, innovation, and career development. The study of work passion has provided valuable insight into the importance of this psychological factor in creating a productive and fulfilling work environment, as well as providing a solid basis for developing an effective human resource management strategy. the discussion on Work Passion is still very relevant to be discussed. So in the end the purpose of this Systematic Literature Review is to find out how the theory and findings of Work Passion have developed in the last ten years, especially in the organizational and medical fields. Work passion plays an important role in the development of science, especially in the field of organization. The concept of work passion refers to the high level of passion or enthusiasm that a person feels towards his work. Work passion involves feelings of enthusiasm, deep involvement, and a strong commitment to the task at hand. Individuals who have high work passion tend to exhibit innovative behavior, have high motivation and morale, achieve good performance, have more successful careers, experience high job satisfaction, and provide a more cheerful atmosphere at work. In order to create a work environment that supports work passion, it is important for organizations to pay attention to and manage the factors that affect the level of passion and employee morale. By creating harmonious working conditions, reducing conflict, paying attention to job demands, and managing stress levels, organizations can encourage high levels of work passion among their employees. In the result, high work passion can improve individual performance, organizational productivity, and provide a more positive and dynamic work atmosphere